Deception Point - Brown, Dan (London Corgi Books, 2004)
Rachel Sexton works for the National Reconnaissance Office as an intelligence officer. She is also the daughter of a Senator currently running for President. Her father's main offensive, and a very popular one, against the incumbent President is to attack the huge amount of NASA funding. Rachel is barely on speaking terms with her father, believing him to be totally corrupt, but is still worried she is being used by the President when he asks her to verify an amazing find by NASA, a find which will settle the arguments about NASA funding for ever. Reluctantly agreeing to view the find Rachel is whisked off to the North Pole. What she finds once she gets there takes her breath away. However, she quickly learns that nothing is what it seems, and, with two civilian scientists, is soon fleeing for her life. Stranded on an ice berg they are rescued in the nick of time by a nuclear submarine, but once back in the US their attempts to expose the plot show them that they can trust absolutely no one...
Keywords: Conspiracies -- Scientists -- Americans